Implementasi Manajemen Bandwidth Hierarchical Token Bucket (HTB) Menggunakan Metode Network Development Life Cycle (NDLC) - Prayitno, Moh. Asy Syam Iriansyah; Rahman, Miftahur; Pater, Dewi Lusiana (BIOS : Jurnal Teknologi Informasi dan Rekayasa Komputer, 2024)
SMKN 1 Klakah is one of the educational institutions in Kab. Lumajang requires an internet network to support the learning process for teachers or students. With adequate internet, it can make it easier for teachers and students to access learning materials. There are times when using the SMKN 1 Klakah Internet network causes poor Internet performance when users access the Internet simultaneously. In addition, the download and upload volume for each user is not distributed evenly, so bandwidth management is required. One method that can stabilize the distribution of bandwidth is the Hierarchical Token Bucket (HTB) method. The research was conducted based on the Network Development Life Cycle (NDLC) model with 6 stages, namely: analysis, design, simulation prototyping, implementation, monitoring and management. Resulting in research that the implementation of the HTB method for bandwidth management in the SMKN 1 Klakah Computer Network Lab was successfully implemented. It was proven that when testing the bandwidth it was in accordance with the specified limit. Also when the QoS test was carried out it was in the good category, as evidenced by the QoS test results on the delay parameters with a value of 5,6 ms, jitter with a value of 4,04 ms, throughput with an average value of 0,921 Mbit, and packet loss with a value of 0%.